Sonates pour le Piano-forte composées par Louis van Beethoven. No. [4]. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Altona; H. Böie; Germany, 2022)
Mid-nineteenth century edition of the Piano Sonata no. 13 in E-flat major, op. 27, no. 1, published by H. Böie in Altona as no. 4 of the collection "Sonatas pour le piano-forte composées par Louis van Beethoven."